Problematika Pelaksanaan Asesmen Kompetensi Minimum Literasi Siswa Kelas VIII di SMP YP PGRI 3 Makassar - Sari, Nofita; Ramly, Ramly; Haliq, Abdul (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study examines various problems that arise in the implementation of the Minimum Competency Assessment (AKM) for eighth-grade students at SMP YP PGRI 3 Makassar. This study aims to describe the problems faced by schools, teachers, and students in implementing the literacy AKM. This study used a descriptive qualitative method. The data and data sources used were primary and secondary data. Data collection techniques used were interviews and documentation. Data validity in this study included persistent observation, triangulation, dependability, and confirmability. Data analysis techniques used data reduction, data presentation, and conclusion drawing. The results of this study indicate that the problems in implementing the Minimum Competency Assessment for eighth-grade students at SMP YP PGRI 3 Makassar include aspects of facilities and infrastructure, lack of teacher training, difficulties in delivering teaching materials, student attendance, lack of AKM exercise books, difficulty in working on questions, and too little time.